The predictive ability of bleeding risk stratification models in very old patients on vitamin K antagonist treatment for venous thromboembolism: results of the prospective collaborative EPICA study. Issue 6 (3rd July 2013) - Poli, D.; Antonucci, E.; Testa, S.; Cosmi, B.; Palareti, G.; Ageno, W.; ,
Summary Background The optimal duration of anticoagulant treatment after venous thromboembolism (VTE) should be evaluated in relation to bleeding risk. This assessment is particularly difficult with elderly patients, because of their increased risk of both recurrences and hemorrhages. Bleeding risk stratification models have been proposed, but their predictive ability in very elderly patients is unknown. We aimed to assess six bleeding stratification models in this setting, by using information available in our dataset. Patients and methods Patients aged ≥ 80 years receiving vitamin K antagonists (VKAs) for the secondary prevention of VTE were eligible for this prospective cohort study. All patients were followed at Italian anticoagulation clinics for monitoring of VKA treatment. Risk factors for bleeding were collected, and major bleeding events and mortality were documented during follow‐up. The association of bleeding events with the available risk factors was tested by means of Cox regression analysis; the c‐statistic was used to quantify the predictive validity of the classification schemes. Results A total of 1078 patients (37.2% males; mean age, 84 years) were enrolled in the study, for a total observation period of 1981 patient‐years. The rate of major bleeding was 2.4 per 100 patient‐years (47 events; one was fatal). The mortality rate was 5.2 per 100 patient‐years. None of the considered risk factors were significantly associated with bleeding events. The predictive validity of the risk stratification models was low, and the most accurate model was not specifically developed for VTE patients (HEMORR2HAGES, c‐statistic 0.60, 95% confidence interval 0.49–0.70). Conclusions Bleeding risk stratification models appear to have little accuracy in very elderly VTE patients.